Model outlining skill builders for Filipino high school students - Doronila, Maria Luisa (Canieso) 1940- ([Quezon City s.n.], 1974)
This study primarily sought to develop model outlining skill builders for all levels in high school. The development of a model outlining skill builder includes the following: (1) summary of procedures for the construction of similar exercises (2) reading materials to be used and (3) model outlining exercises. The study also aimed to formulate a design for the sequential development of the skill of outlining which includes (1) identification of the skills component to outlining (2) formulation of a scope and sequence of skills at each level of difficulty and (3) formulation of guidelines for the selection and preparation of reading materials to be used.
Thesis (M.Ed.)--University of the Philippines.
Keywords: English language -- Composition and exercises